IMPROVE THE ABILITY TO FIND OPINIONS AND RESULTS OF LEARNING IPS THROUGH LEARNING MODEL PROBLEM BASED LEARNING IN CLASS VIII STUDENTS SUMALATA STATE 3RD PRIVATE VOCATIONAL SCHOOL NORTH GORONTALO DISTRICT - SARIPIN SARIPIN (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Luwuk, 2019)
The purpose of this study was to determine the improvement in the ability to express opinions and social studies learning outcomes through the Problem Based Learning learning model in learning in class VIII Sumalata State Junior High School 3 North Gorontalo Regency. The subjects in this study were 24 people, 13 were male students and 11 were female students. Data analysis is done through analysis of the results of observations and the results are used to reflect on whether students have been able to improve the ability to express opinions and learning outcomes. The results of this analysis will be used to plan actions for each cycle. The results showed that in the first cycle the ability to express student opinions increased to 73% and learning outcomes increased to 71% and in cycle II the ability to express student opinions increased to 88% and learning outcomes increased to 88%. Keywords:Problem Based Learning, ability to express opinions and learning outcomes